Inovasi Pelayanan Publik Terintegrasi dalam Satu Lokasi: Studi Kasus Mal Pelayanan Publik (MPP) Surabaya - Aisyah Febriyanti; Yulia Sri Kanti; Shany Gupa Pratama; Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This research examines the implementation of the Surabaya Public Service Mall (MPP) as an integrated public service innovation. Using a qualitative approach with case studies and library research methods, this research analyzes the formation process, characteristics, advantages, as well as the impacts and obstacles of MPP Surabaya. The research results show that MPP Surabaya has succeeded in integrating more than 600 types of services from 43 central and regional agencies in one location. MPP Surabaya's advantages include service integration, digitalization and automation, adequate supporting facilities, as well as speed and transparency of service. The resulting positive impacts include ease of access for the public, cost and time efficiency, and increased public trust in government institutions. However, the implementation of MPP Surabaya also faces obstacles in the form of communication challenges between agencies and technical problems on the server. This research concludes that MPP Surabaya has become a model of public service innovation which has resulted in a change in the bureaucratic paradigm to be more responsive to community needs.